1980
DOI: 10.1159/000145352
|View full text |Cite
|
Sign up to set email alerts
|

Sensorivagal nature of oesophageal submucous layer nerve endings

Abstract: Two types of surgery were performed on domestic cats to establish the source and functional significance of the apparatuses we have denominated perivascular, perifascicular and free endings of the oesophageal submucous layer. After extirpation of the cranial regions of the sympathetic ganglionic chain, of all the cervical ganglia and of the four proximal thoracic ganglia, no Wallerian degeneration of the concerned nerve endings was observed, thus ruling out their dependence on this neural pathway. After ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The existence of type II perivascular and type III submucosal laminar endings suggests that there are additional parameters to be detected by vagal afferent neurons, e.g., arterial pulsations or venous filling states. These perivascular and submucosal sensors were similar to the perivascular and submucosal sensors in the esophagus of the cat, as described by Rodrigo et al (1970Rodrigo et al ( , 1980. Perivascular endings in the submucosa of the esophagus resembled vagal afferent terminal structures in the wall of the aortic arch and its main branches in the guinea pig, most likely representing baroreceptors (Quigg, 1991).…”
Section: Peripheral Innervation Patterns Are Reflected At Ganglionic supporting
confidence: 79%
“…The existence of type II perivascular and type III submucosal laminar endings suggests that there are additional parameters to be detected by vagal afferent neurons, e.g., arterial pulsations or venous filling states. These perivascular and submucosal sensors were similar to the perivascular and submucosal sensors in the esophagus of the cat, as described by Rodrigo et al (1970Rodrigo et al ( , 1980. Perivascular endings in the submucosa of the esophagus resembled vagal afferent terminal structures in the wall of the aortic arch and its main branches in the guinea pig, most likely representing baroreceptors (Quigg, 1991).…”
Section: Peripheral Innervation Patterns Are Reflected At Ganglionic supporting
confidence: 79%
“…The existence of type II perivascular and type III submucosal laminar endings suggests that there are additional parameters to be detected by vagal afferent neurons, e.g., arterial pulsations or venous filling states. These perivascular and submucosal sensors were similar to the perivascular and submucosal sensors in the esophagus of the cat, as described by Rodrigo et al (1970, 1980). Perivascular endings in the submucosa of the esophagus resembled vagal afferent terminal structures in the wall of the aortic arch and its main branches in the guinea pig, most likely representing baroreceptors (Quigg, 1991).…”
Section: Discussionmentioning
confidence: 93%
“…Morphological studies of the mucosal innervation in the oesophagus have been carried out for a while (Cecio & Califano, 1967; Rodrigo et al 1975 a , b , 1980) using anterograde neuronal tracing in the lower (Clerc & Condamin, 1987) and a combination of tracing and immunohistochemistry for calcium binding proteins in the upper oesophagus (Dutsch et al 1998). Retrograde tracing experiments in this region showed that ∼80% of the petrosal and jugular neurons express calcitonin gene‐related peptide (CGRP), a neuropeptide typically found in small diameter spinal nociceptors (Rosenfeld et al 1983; Traub et al 1990).…”
Section: Discussionmentioning
confidence: 99%